Breast Cancer and Resilience: The Controversial Role of Perceived Emotional Intelligence - Guil, Rocio; Ruiz-González, Paula; Merchán-Clavellino, Ana; Morales-Sánchez, Lucía; Zayas, Antonio; Gómez-Molinero, Rocio (Frontiers in Psychology, 2020)
Cancer is a chronic disease that causes the most deaths in the world, being a public health problem nowadays. Even though breast cancer affects the daily lives of patients, many women become resilient after the disease decreasing the impact of the diagnosis. Based on a positive psychology approach, the concept of co-vitality arises understood as a set of socio-emotional competencies that enhance psychological adaptation. In this sense, emotional intelligence is one of the main protective factors associated with resilience. However, it is not always as beneficial as it seems, and can lead to collateral effects on psychological adjustment. Given this controversy, this study aims to find the specific processes through which the dimensions of Perceived Emotional Intelligence (PEI) (Emotional Attention, Emotional Clarity, and Mood Repair) can act as a risk or protective factor in the development of resilience. The total sample was 167 women (Age: M=43.26; SD=12.43), 46.7% were breast cancer survivors and 53.3% were healthy controls. The selection of women with breast cancer was carried out randomly, recruited through the Oncology Units. The sample completed measures of resilience and PEI, through Resilience Scale (Wagnild & Young, 1993) and TMMS-24 (Salovey, Mayer, Goldman, Turvey, & Palfai, 1995). The results showed that breast cancer survivors showed higher age and greater levels of resilience and mood repair than healthy women. The mediation analysis revealed that breast cancer survival and PEI predicted 28% of the variance of resilience. The direct effects showed that emotional clarity and mood repair increased resilience levels. Although breast cancer did not predict resilience directly, it does through mood repair by an indirect process. Besides, the analysis showed that emotional attention played a role in vulnerability, decreasing mood repair, and resilience. These research support theories that point to a possible dark side of PEI. Thus, a great level of emotional attention makes dark the positive effect of mood repair and personal growth if it is not complemented by a clear perception of emotions. These results provide empirical support concerning the need to work complementary each dimension of PEI to avoid unwanted effects on intrapersonal adjustment.